Design and synthesis of small molecular 2-aminobenzoxazoles as potential antifungal agents against phytopathogenic fungi - Fan, Lingling (Mol Divers, 2021)
In order to discover novel antifungal agents, three series of simple 2-aminobenzoxazole derivatives were designed, synthesized and evaluated for their antifungal activities against eight phytopathogenic fungi. The in vitro antifungal results showed that most of the target compounds exhibited excellent and broad-spectrum antifungal activities to all the tested fungi. Particularly, the six compounds 3a, 3b, 3c, 3e, 3m and 3v displayed the most potent antifungal activity, with EC(50) value of 1.48–16.6 µg/mL, which were much superior to the positive control hymexazol. The in vivo study further confirmed that compounds 3a, 3c, 3e and 3m displayed good preventative effect against Botrytis cinerea at the concentration of 100 µg/mL. The structure–activity relationships research provides significant reference for the further structural optimization of 2-aminobenzoxazole as potential fungicides. GRAPHIC ABSTRACT: Forty-four 2-aminobenzoxazole derivatives were designed and synthesized as agricultural antifungal agents, the in vitro and in vivo antifungal experiments showed that compounds 3a, 3b, 3c, 3e, 3m and 3v exhibited excellent and broad-spectrum antifungal activities compare with the commercial fungicide hymexazol. [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11030-021-10213-7.